Inflammatory signaling in cartilage: MAPK and NF-kappaB pathways in chondrocytes and the use of inhibitors for research into pathogenesis and therapy of osteoarthritis. - Saklatvala, J (2007)
Osteoarthritis is characterised by degeneration of articular cartilage. It is thought to be primarily a disease of cartilage. Inflammatory response genes, such as proteinases, cyclooxygenase, and cytokines are implicated in its pathogenesis. The evidence for expression of these genes in articular cartilage in osteoarthritis is reviewed. The expression of inflammatory response genes is controlled by four major intracellular signalling pathways. These lead to activation of the three mitogen-activated protein kinases (MAPK) and the transcriptional regulator nuclear factor kappa (NFkappa)-B. The current state of knowledge of the structure of these pathways is summarized. Pharmacological inhibitors of the protein kinases of the pathways in current use are described, and insights into chondrocyte gene expression obtained with them are discussed. Very limited use of these inhibitors has yet been made in animal models of osteoarthritis. The main use of the inhibitors in the near future will be in investigation of pathogenetic mechanisms in osteoarthritis, both in experimental animals and in vitro, with a view to identifying therapeutic targets. Prospects for using signalling pathway inhibitors for therapy in osteoarthritis are distant.